Cover Picture: Ann. Phys. 1‐2'2015. Issue 1 (January 2015) - Harris, Jack; Rabl, Peter; Schliesser, Albert
<x xml:space="preserve">Abstract</x> Mechanical devices that exploit micro/nano‐fabrication as well as integration into other ultrasensitive transducers – optical, electronic, or atomic – have opened intriguing new avenues of research. These devices provide new means for cooling, signal processing, and sensing of electric, magnetic, and gravitational fields. With many of these systems now entering the quantum regime, their possible use in quantum engineering – for state storage, transduction and conversion – is explored. Beyond engineering, mechanical oscillators also provide especially clear realizations of quantum measurement processes, and may ultimately enable new insights into fundamental limits arising from decoherence of these unprecedentedly massive quantum objects. Picture credits: Albert Schliesser/EPFL <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>